2022
DOI: 10.1111/nyas.14790
|View full text |Cite
|
Sign up to set email alerts
|

The forgotten role of absorption in music reward

Abstract: Interindividual differences in music-related reward have been characterized as involving five main facets: musical seeking, emotion evocation, mood regulation, social reward, and sensory-motor. An interesting concept related to how humans decode music as a rewarding experience is music transcendence or absorption (i.e., musicdriven states of complete immersion, including momentary loss of self-consciousness or even time-space disorientation). Here, we investigated the relation between previously characterized … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 94 publications
2
28
0
Order By: Relevance
“…These, along with their altered versions, resulted in eight unique melodies presented to participants in this study. Participants also completed an updated version of the BMRQ: the extended Barcelona Music Reward Questionnaire (eBMRQ), which includes an additional sixth factor (4 additional items) which measures experiences of absorption in music listening (Cardona et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These, along with their altered versions, resulted in eight unique melodies presented to participants in this study. Participants also completed an updated version of the BMRQ: the extended Barcelona Music Reward Questionnaire (eBMRQ), which includes an additional sixth factor (4 additional items) which measures experiences of absorption in music listening (Cardona et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…These, along with their altered versions, resulted in eight unique melodies presented to participants in this study. Participants also completed an updated version of the BMRQ: the extended Barcelona Music Reward Questionnaire (eBMRQ), which includes an additional sixth factor (4 additional items) which measures experiences of absorption in music listening (Cardona et al, 2022). Procedure Participants underwent the same procedure as previous studies, with the exception that melodies were presented either 0, 4, 10, or 14 times during the exposure phase and that there was only one melody assigned to each condition.…”
Section: Study 5 Participantsmentioning
confidence: 99%
“…In addition, from the perspective of people's subjective feelings, music affects people's hearing through the sound effect, and then the audience makes a judgment on this kind of hearing, is happy, sad, thinking, or sad, and then brings an impact on people's intuition and other feelings, and even affects people's feelings and thoughts. Marxism holds that everything is interrelated and complementary with other things except for its own independence, and music is the same [ 3 , 4 ]. In the analysis and research of music, music cannot be independent but should be combined with related things for analysis, which plays an important role in our comprehensive and in-depth understanding of music.…”
Section: Introductionmentioning
confidence: 99%
“…Here we characterize for the first time age-related differences in the neural substrates of musical reward. These data provide insight into the mechanisms underlying observed differences in musical reward in young and older adults (Belfi et al, 2020;Cardona et al, 2022;Mas-Herrero et al, 2013), characterize the contributions of auditory and reward networks during Univariate analyses showed that both young and older adults activated multiple regions within the auditory network during music listening, as well as the mPFC during music listening that was rated as loved. The engagement of mPFC when listening to preferred music is consistent with its observed role in musical reward processing (Salimpoor et al, 2013).…”
Section: Discussionmentioning
confidence: 95%
“…The copyright holder for this preprint this version posted January 2, 2023. ; https://doi.org/10.1101/2023.01.01.522417 doi: bioRxiv preprint adults than in young adults (Belfi et al, 2021;Cardona et al, 2022). Addressing these gaps in our understanding of age-related differences in reward and functional network dynamics will have implications for the design of music-based interventions for healthy aging.…”
Section: Introductionmentioning
confidence: 99%